Feasibility justification of implementation of a device for sorting sheep products in the context of industry development - Tsybukh, Andrii; Kravchenko, Olha; Pomitun, Ivan; Lysychenko, Mykola (Technology audit and production reserves, 2021)
The object of research is the methodology of a feasibility study for the introduction of a device for sorting sheep products. Sheep products mean sheep wool, the sorting accuracy of which affects the formation of the sale price of the final product (wool), including the size of the manufacturer’s profit, respectively, and the effectiveness and the level of economic efficiency of production. One of the most problematic areas is the subjective assessment of wool quality at the stage of pricing policy formation. This criterion is determined by a set of physical and technological indicators, which include the color of the coat, due to the degree of its melanin pigmentation or yellowing. Such an assessment, at present, is carried out with the participation of the operator, without the involvement of technical means capable of objectively registering and further providing data for the successful selection of sheep and the sale of wool. In the course of the study, a systematic approach to the study of technical and economic processes and phenomena, an abstract logical method, monographic and empirical methods, a comparative analysis method, tabular and graphical methods, as well as a computational and constructive method for substantiating technical and economic indicators of the effectiveness of device implementation were used. The proposed analysis of the implementation of the device allows specialists at the level of enterprises producing sheep products to optimize the formation and implementation of the pricing policy. And it can also be used at the level of government bodies in determining the national policy for the development of sheep breeding and the formation of a strategy for its development. The obtained results of implementation allow: – to increase the profit for each head of animals from the sale of better quality wool; – to increase the level of profitability, which makes it possible to ensure the payback period for additional capital expenditures of less than two years; – to confirm the economic feasibility of using this equipment, since the payback period for additional capital costs does not exceed two years, and the discounted payback period does not exceed the useful life.